Tenofovir disoproxil fumarate directly ameliorates liver fibrosis by inducing hepatic stellate cell apoptosis via downregulation of PI3K/Akt/mTOR signaling pathway - Lee, Sung Won; Kim, Sung Min; Hur, Wonhee; Kang, Byung-Yoon; Lee, Hae Lim; Nam, Heechul; Yoo, Sun Hong; Sung, Pil Soo; Kwon, Jung Hyun; Jang, Jeong Won; Kim, Seong-Jun; Yoon, Seung Kew (PLOS ONE, 2021)
Background Antifibrotic agent for the treatment of liver fibrosis has not been developed so far. Long term treatment of chronic hepatitis B patients with antiviral drugs tenofovir disoproxil fumarate (TDF) and entecavir (ETV) results in the regression of liver fibrosis, but the underlying mechanism has not been clarified. Therefore, we aimed to investigate the direct impact of TDF and ETV on liver fibrosis. Methods Activated hepatic stellate cell (HSC) cell lines were used to evaluate the effects of TDF and ETV. After treatment with each antiviral agent, cell viability, morphology, apoptotic features, autophagy and antifibrosis signalling pathways were examined. Then, collagen deposition, fibrosis markers and activated HSCs were measured in liver tissues of the liver fibrosis model mice. Results After TDF treatment, the viabilities of LX2 and HSC-T6 cells were decreased, and the cells exhibited apoptotic features, but ETV did not induce these effects. Cleavage of PARP and Caspase-3 and the inhibition of the antiapoptotic gene Bcl-xl indicated activated HSC apoptosis following TDF treatment. TDF simultaneously increased autophagy, which also regulated apoptosis through crosstalk. TDF inactivated the PI3K/Akt/mTOR signalling pathway, which was associated with the activation of both apoptosis and autophagy. In the liver fibrosis mouse model, the fibrotic area and activated HSC markers were decreased by TDF but not ETV treatment. Additionally, apoptotic cells were concentrated in the periportal fibrotic area after TDF treatment, which indicated the specific antifibrotic effect of TDF. Conclusions TDF directly ameliorates liver fibrosis by downregulating the PI3K/Akt/mTOR signalling pathway, which results in the apoptosis of activated HSCs. The antifibrotic effects of TDF indicate that it may be a therapeutic agent for the treatment of liver fibrosis.